2016
DOI: 10.1371/journal.pone.0163327
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Bcl-2/Bax Proteins and the Mitochondria-Mediated Apoptosis Pathway in the Differentiation of Adipose-Derived Stromal Cells into Neurons

Abstract: Our objective is to study the relationship between the regulatory proteins Bcl-2/Bax and mitochondria-mediated apoptosis during the differentiation of adipose-derived stromal cells (ADSCs) into neurons. Immunocytochemistry and western blotting showed that the cells weakly expressed neuron-specific enolase (NSE) in the non-induced group and expressed NSE more strongly in the groups induced for 1 h, 3 h, 5 h and 8 h. NSE expression peaked at 5 h (P < 0.05), although there was no significant difference between 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
91
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(94 citation statements)
references
References 14 publications
(14 reference statements)
3
91
0
Order By: Relevance
“…The generation of ROS, however, may result in an imbalance in the intracellular redox status, which then allows ROS to mediate MMP transition, mitochondrial release of cytochrome c into the cytosol, and caspase activation. The proapoptotic Bax protein induces mitochondrial dysfunction and cytochrome c release from the mitochondrion that interacts with a specific adapter, which in turn activates pro‐caspases to active caspases . We evaluated CGs capable of inducing the mitochondrial release of cytochrome c and alteration of Bax from the cytosol into mitochondria, and thus, evaluated MMP loss in the process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The generation of ROS, however, may result in an imbalance in the intracellular redox status, which then allows ROS to mediate MMP transition, mitochondrial release of cytochrome c into the cytosol, and caspase activation. The proapoptotic Bax protein induces mitochondrial dysfunction and cytochrome c release from the mitochondrion that interacts with a specific adapter, which in turn activates pro‐caspases to active caspases . We evaluated CGs capable of inducing the mitochondrial release of cytochrome c and alteration of Bax from the cytosol into mitochondria, and thus, evaluated MMP loss in the process.…”
Section: Discussionmentioning
confidence: 99%
“…The proapoptotic Bax protein induces mitochondrial dysfunction and cytochrome c release from the mitochondrion that interacts with a specific adapter, which in turn activates pro-caspases to active caspases. 46 We evaluated CGs capable of inducing the mitochondrial release of cytochrome c and alteration of Bax from the cytosol into mitochondria, and thus, evaluated MMP loss in the process. Moreover, NAC prevents Bcl-2 downregulations and protects against MMP loss, thus protecting cells from ROS and apoptotic cell death ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%
“…It also suggested that AS‐IV increased mitochondrial energy production. Bcl‐2 and Bax play a very important role in apoptosis (Korsmeyer, Shutter, Veis, Merry, & Oltvai, ) and also are critical in regulating the effects of mitochondrial membrane permeability (Wang et al, ) and mitochondrial respiratory chain function (Luo et al, ). A study showed that AS‐IV upregulated Bcl‐2 expression in cardiomyocytes (Luo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the phenomenon of cell cycle-mediated apoptosis has also received increasing attention and is an appre- ciated approach to eliminate cancer cells. 38,39) In this regard, cinobufagin is a promising chemical because it is capable of selectively or preferentially killing cancer cells by inhibiting cell cycle progression and/or inducing apoptosis. [21][22][23][24][25][26][27] This study initially revealed that cinobufagin treatment induced apoptosis of EC-109, Kyse-150 and Kyse-520 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%